2018
DOI: 10.1039/c7ta08423d
|View full text |Cite
|
Sign up to set email alerts
|

Fe/Fe3C@C nanoparticles encapsulated in N-doped graphene–CNTs framework as an efficient bifunctional oxygen electrocatalyst for robust rechargeable Zn–air batteries

Abstract: 3d transition metals or their derivatives encapsulated in nitrogen-doped nanocarbon show promising potential in non-precious metal oxygen electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
151
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 383 publications
(157 citation statements)
references
References 58 publications
4
151
0
2
Order By: Relevance
“…Notably,t he porous carbon surface obtained at ap yrolysis temperature of 850 8Cw as interwove with bamboo-like carbon nanotubes (Figures 1a andS 3g), which is considered to be an excellent heterostructure for catalysis. [38,39] As shown in Figure S3 d, there are about twenty Co NPs in Co-NSPC-550. As the pyrolysis temperature was increased from 700 to 1000 8C, Co NPs werec learly observed with increasing sizes from 15.26 to 24.93 nm (Figure 1d and S3 f, h).…”
Section: Resultsmentioning
confidence: 98%
“…Notably,t he porous carbon surface obtained at ap yrolysis temperature of 850 8Cw as interwove with bamboo-like carbon nanotubes (Figures 1a andS 3g), which is considered to be an excellent heterostructure for catalysis. [38,39] As shown in Figure S3 d, there are about twenty Co NPs in Co-NSPC-550. As the pyrolysis temperature was increased from 700 to 1000 8C, Co NPs werec learly observed with increasing sizes from 15.26 to 24.93 nm (Figure 1d and S3 f, h).…”
Section: Resultsmentioning
confidence: 98%
“…The obtained results proved a higher catalytic activity for the composite electrode, with respect to pure Pt/C, in terms of electrochemically active surface area, oxygen reduction current density, onset potential and stability.Oxygen electrochemistry plays a key role either in energy conversion or in energy storage, because of its importance in several technologies, such as fuel cells and metal-air batteries, both in acid and alkaline environment. [1][2][3][4] Although Pt/C catalysts are widely used as oxygen electrode, there is the need to find new, efficient, stable and less expensive materials to be used as cathodes. [5][6][7] Considerable efforts in the last decade were addressed to improve the electrochemical oxygen reduction reaction and to reduce Pt loading, in order to achieve lowcost targets.…”
mentioning
confidence: 99%
“…Carbon nanotubes (CNTs), consisting of at hin planar sheet of sp 2 -bonded carbon atoms denselyp acked in ah oneycomb crystal lattice, were first reportedb yL ijima in 1991. [1] Due to their high surfacea rea and excellent electronic conductivity, [2][3][4][5][6] CNTsa re good supports for metals to promote chemical reactions. Severalr eports in the literature have shown that CNTsupported transition metals exhibit much-enhanced activity in oxygen reduction reactions (ORRs).…”
Section: Introductionmentioning
confidence: 99%